1970
DOI: 10.2307/1217958
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Classification of the Homosporous Ferns

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. International Association for Plant Taxonomy (IAPT) is collaborating with JSTOR to digitize, preserve and extend access to Taxon.More than probably any other group of plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1973
1973
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 3 publications
0
29
0
1
Order By: Relevance
“…However, Holttum [4] made tectarioids a subfamily (Tectarioideae) of Dennstaedtiaceae. Among polypods, close relationship between Tectariaceae and Dryopteridaceae has not been questioned substantially; both groups were placed in different subfamilies [5] , different tribes [6] or even in one tribe [7,8] . In the systematic arrangement of the Chinese fern families and genera, Ching [9] treated Dryopteridaceae and Tectariaceae as closely related but distinct families.…”
mentioning
confidence: 99%
“…However, Holttum [4] made tectarioids a subfamily (Tectarioideae) of Dennstaedtiaceae. Among polypods, close relationship between Tectariaceae and Dryopteridaceae has not been questioned substantially; both groups were placed in different subfamilies [5] , different tribes [6] or even in one tribe [7,8] . In the systematic arrangement of the Chinese fern families and genera, Ching [9] treated Dryopteridaceae and Tectariaceae as closely related but distinct families.…”
mentioning
confidence: 99%
“…Observations are reported on the spores of Cheilanthes farinosa (sexual diploid), a homosporous fern, belonging to the family Cheilanthaceae, order Schizaeales (12). The spores were collected from Chandigarh, India in the fall of 1971 and held in storage at 4 C. They were sown on the surface of 10 ml of a mineral salt medium (15) contained in 5 cm diameter Petri dishes, and allowed to imbibe in the dark for 4 days before irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Baker, D. novo-guineae Christ (incl. D. crassifolium Brause), and D. piloselloides (Christensen, 1929;Copeland, 1947;Nayar, 1970;Pichi Sermolli, 1977a, 1977. Ravensberg and Hennipman (1986) studied the morphology and anatomy of all five species and related species of Pyrrosia and found that Drymoglossum is not monophyletic, but three out of the five species, D. heterophyllum, D. niphoboloides and D. piloselloides, did form a monophyletic group.…”
Section: Resolution Of Drymoglossummentioning
confidence: 99%
“…(Fig. 1A and B), and the three genera had been placed in subfamily Platycerioideae (Nayar, 1970). Additionally, Platycerioideae is characterized by two potential synapomorphies, heavily sclerified rhizomes and lack of pinnate dissection (Hovenkamp, 1986;Hennipman, 1990).…”
Section: Introductionmentioning
confidence: 99%